REFLEKSI PENERAPAN TEKNOLOGI INFORMASI DAN KOMUNIKASI DALAM PENDIDIKAN DI INDONESIA - Murti Kusuma Wirasti (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2007)
As global social, economic and politic competition grows sharper, education becomes an important source of competitive advantage. Information and Communication Technology (ICT) is one of the main part for learning process improvement in Indonesia. Getting the best from ICT depends on several variables, including the appropriate design of hard technology, soft technology, and content; the training and attitude of instructors; and the realization that different students have different requirements. But we must respond critically and wisely. ICT is produced by some countries with several goals to get advantages from developing countries which have placed ICT as an important factor for human welfare improvement, closely linking with educational system. A decision made to use ICT in learning system must consider several factors consciously, such as socio-cultural and economic capabilities of our society. That is an approach to maintain our goals as free as developed countries in using ICT for education.